2007
DOI: 10.1111/j.1744-7429.2007.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Large Tree Density on Howler Monkey (Alouatta palliata mexicana) Presence in Very Small Rain Forest Fragments

Abstract: The populations of the Mexican mantled howler monkey (Alouatta palliata mexicana) in the Los Tuxtlas region, Mexico, have declined drastically due to habitat loss and fragmentation. Nevertheless, several troops still inhabit very small and isolated rain forest fragments. We identified the main vegetation attributes that can favor the presence of howlers within 18 small (< 10-ha) fragments that did not differ significantly in size, shape, and isolation (nine occupied and nine unoccupied by howlers). We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 58 publications
4
64
0
9
Order By: Relevance
“…However, in accordance to our results, other studies found smaller abundance of some palm species in more degraded forests (Arroyo-Rodríguez et al, 2007a;Baez and Balslev, 2007). Forest structure may also influence the occurrence and abundance of seed dispersers (Balcomb et al, 2000;Arroyo-Rodríguez et al, 2007b). Taller forests, with larger trees and closed canopy resemble forests in a later stage of succession, which could retain a larger fraction of the original frugivore guild.…”
Section: Discussionsupporting
confidence: 90%
“…However, in accordance to our results, other studies found smaller abundance of some palm species in more degraded forests (Arroyo-Rodríguez et al, 2007a;Baez and Balslev, 2007). Forest structure may also influence the occurrence and abundance of seed dispersers (Balcomb et al, 2000;Arroyo-Rodríguez et al, 2007b). Taller forests, with larger trees and closed canopy resemble forests in a later stage of succession, which could retain a larger fraction of the original frugivore guild.…”
Section: Discussionsupporting
confidence: 90%
“…Only 5% consists of continuous rainforest at high elevations (>800 m) [25]. As a result, the remaining population is spread across archipelagoes of forest fragments that vary in size, isolation distance, age, and quality, resulting in precarious demographic and ecological conditions [26][27][28][29]. Studies at Los Tuxtlas have shown that the presence and abundance of howlers monkeys are positively related to fragment size and quality, and negatively related to fragment isolation [18,19,25,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The IVI is an indicator of the species importance in the tree community and is calculated by the sum of the species density (number of individuals of species x / area sampled), frequency (number of transects in which species x occurs / total number of transects) and dominance (total basal area of the species in the sampled area). The higher the value of the IVI, the higher the importance of species in the tree community [33].…”
Section: Vegetation Surveymentioning
confidence: 99%